2017
DOI: 10.18632/oncotarget.21250
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of inducible nitric oxide synthase and mitochondrial dysfunction in the pathogenesis of enterovirus 71 infection

Abstract: Enterovirus71 (EV71) is recognized as the main causative agent of severe hand, foot and mouth disease (HFMD). However, the pathogenesis of EV71 infection has not been well characterized. Clinical evidence indicated that inducible nitric oxide synthase (iNOS) induction in the lung of HFMD patients contributes to the severe symptoms of pulmonary edema. In the present study, we recruited 142 subjects including HFMD patients and controls, and serum level of nitric oxide (NO) was determined. Next, cellular and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…To further confirm the involvement of RAS in the pathogenesis of HFMD, we establish an EV71-infected mouse model [14,15]. In our study, we found that EV71 infection induced Ang II and NA expression in the brains, skeletal muscle, and lungs of EV71-infected mice.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…To further confirm the involvement of RAS in the pathogenesis of HFMD, we establish an EV71-infected mouse model [14,15]. In our study, we found that EV71 infection induced Ang II and NA expression in the brains, skeletal muscle, and lungs of EV71-infected mice.…”
Section: Discussionmentioning
confidence: 62%
“…BALB/c mice (SPF degree) were purchased from the Medical Animal Center in Zhengzhou University, Henan, China, and raised in individual ventilation cage (IVC) system. As described in our previous study [14,15], 3-day-old BALB/c mice were i.p. inoculated with EV71 strain (2×10 6 pfu/mouse) and sacrificed with isoflurane anesthesia on 3, 5 and 7 days post infection (dpi).…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, EV71 strain (ZZ1350) was isolated from a nonfatal case with CNS involvement in Children's Hospital of Zhengzhou (Zhengzhou, Henan, China) [17]. Virus purification was conducted as previously described [18].…”
Section: Virus and Cellsmentioning
confidence: 99%
“…Toluidine blue stained lung slices were observed under optical microscope, and the number of toluidine blue-positive cells per mm 2 was quantified in a blinded fashion using ×20 magnification. The viral VP1 antigens were detected by immunohistochemical (IHC) staining as described previously [17].…”
Section: Histopathological and Immunohistochemical Analysismentioning
confidence: 99%